Effect of Self-Regulated Learning for Improving Dietary Management and Quality of Life in Patients with Type-2 Diabetes Mellitus at Dr. Ramelan Naval Hospital, Surabaya, Indonesia - Estuningsih, Yayuk; Rochmah, Thinni Nurul; Andriani, Merryana; Mahmudiono, Trias (UI Scholars Hub, 2019)
Self-regulated learning is a process of learning how to manage and regulate oneself to obtain skills and knowledge without depending on others. It is expected that diabetes patients can manage their diabetes by themselves. This study aimed to analyze the effect of self-regulated learning-based educational intervention on quality of life for patients with type-2 diabetes mellitus (DM) at Dr. Ramelan Naval Hospital, Surabaya. This was a quasi-experimental study in the form of pretest and posttest with a control group design. A total of 20 patients with DM were randomly divided into intervention and control groups to undergo a 4-week intervention. The intervention group received dietary education with self-regulated learning, while the control group received standard education. The results revealed differences in variables such as dietary obedience, food intake at home, fasting blood sugar, diastolic blood pressure, and quality of life. The intervention group experienced a positive impact on the quality of life and resulted in better dietary obedience than that of the control group. In conclusion, the implementation of self-regulated learning-based dietary education can improve dietary obedience, knowledge, intention, family support, social support, physical activity, and quality of life for patients with type 2 diabetes.